Preparations and characterization of wolfram doped photocatalyst with mesoporous titanium dioxide (TiO2) via a sol-gel method - Siti Ramlah , Badarudin (2012)
For the past two decades, the research of titanium dioxide was widely developed. The purpose of this study js to synthesize and characterize wolfram doped photocatalyst with mesoporous titanium dioxide (Ti0 2 ) via sol-gel method. The pristine mesoporous titanium dioxide (M-Ti0 2 ) and the doped mesoporous titanium dioxide (doped M-Ti02) were successfully prepared as photocatalysts via a sol—gel method. Surfactant of hexadecyltrimethyl ammoniumbromide (CTAB) was used as a template. The mesoporous titanium dioxide was doped with wolfram (W). Those mesoporous photocatalysts (M-Ti0 2 and doped M-Ti0 2 ) were characterized using thermogravimetric analysis (TGA), X-ray diffraction (XRD) and specific surface area analysis (BET). As a result, XRD showed the doped M-Ti0 2 had smaller particle size compared to M-Ti02 and commercialize titanium dioxide (P-25). For TGA, all the mesoporous titanium dioxides were thermodynamically stable. Besides, in BET, the surface area of doped MTi0 2 increase while the pore size decrease. The performances of the synthesized photocatalysts were measured by the degradation rate of methylene blue using an UV irradiating light of 365 rim by UV—visible spectrometer (UV-vis). The performances for the synthesized mesoporous titanium dioxides (the M-Ti0 2 , and the doped M-Ti02) were much better than P-25. The doped M-Ti0 2 acts better as a photocatalyst rater than pristine M-Ti0 2 . Doping wolfram in the M-Ti0 2 promoted the increase of crystal size and bandgap values of the anatase Ti02.